A Modification of the Cheli Craniolateral Approach for Minimally Invasive Treatment of Osteochondritis Dissecans of the Shoulder in Dogs: Description of the Technique and Outcome in 164 Cases - Vezzoni, Aldo; Vezzoni, Luca; Boiocchi, Silvia; Miolo, Alda; Holsworth, Ian Gordon (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to describe a novel minimally invasive surgical approach for the treatment of shoulder osteochondritis dissecans (OCD) in dogs and to retrospectively review our clinical cases treated with this approach.Study Design The study describes a modification of Cheli surgical approach (1985), developed to reduce the degree of invasiveness as well as the incidence of postoperative complications observed in other surgical approaches to the shoulder joint. Medical records of dogs that underwent our minimally invasive approach to the scapulohumeral joint for treatment of OCD from May 2001 to May 2019 were retrospectively reviewed for intraoperative findings and complications. Clinical outcome and complications were also evaluated in the operated dogs with a minimum of a 2-month-follow-up evaluation.Results A total of 164 shoulders in 141 dogs (23 bilateral), 103 males and 38 females, were examined and treated with our modified craniolateral approach for the treatment of OCD of the humeral head. In all cases, the modified craniolateral approach allowed visibility and adequate exposure of the caudal humeral head surface. Radiographic and clinical follow-up evaluations were available in 123/164 (75%) cases. The clinical outcome was consistent with other reports using different surgical approaches for OCD lesions of the humeral head in dogs.Clinical Significance This technique provided a reliable approach for surgical treatment of canine shoulder OCD and can be considered a valid alternative to other surgical approaches including arthroscopy.
Keywords: osteochondritis dissecans; shoulder; dog; arthrotomy; minimally invasive approach